Pengaruh Kepatuhan Wajib Pajak, Pemeriksaan Pajak, Dan Penagihan Pajak Terhadap Penerimaan Pajak Pengasilan (Pph) Pasal 25/29 Badan Pada Kpp Pratama Balikpapan - Satriawaty Migang; Ruky Dwi Dirmayani (Fakultas Ekonomi Universitas Pekalongan, 2017)
The influence of tax obligation obedience, tax investigation, and tax billing to income tax enrollment clause 25/29 board of KPP Pratama Balikpapan. This examination intended to examine the influence of tax obligation obedience, tax investigation and tax billing to income tax enrollment clause 25/29 board partially and simultaneously. This research contain of one dependent variabel which is income tax enrollment clause 25/29 board and three independent variabel which is influence of tax obligation, tax investigation and tax billing. The sample of this research is the entire research population that is board of tax oligation registered in KPP Pratama Balikpapan in 2013 until 2016. Data analysis technique is double analysis regretion linear method. The result of this research shows that influence of tax examination and tax billing to income tax enrollment clause 25/29 board. While, tax obligation obedience did not influence income tax enrollment clause 25/29 board. However, tax obligation obedience, tax examination, and tax billing have influences to income tax enrollment clause 25/29 board simultaneously.